Negotiating Tīvaevae and Talanoa Methodologies in Education: A Critical Reflection - Houghton, Joseph Bruce Tutonga (Waka Kuaka, 2023)
The diverse nature of Pacific communities in Aotearoa New Zealand means that Pacific educators and researchers regularly negotiate multiple identities, voices and cultures in their work and research. Often researchers in this field emerge from an education or teaching background and wish to explore the questions they have formulated about their local or wider Pacific community with regards to education. This paper offers a reflection from a Cook Island Māori researcher who has negotiated the use of the talanoa and tīvaevae methodologies as part of his participatory action research doctoral study. The researcher’s experience indicates a dynamic synergy between the two methods, as they pertain to the Pacific educational research field in New Zealand. The reflection offered aims to help inform and support other researchers, Pacific and non-Pacific, in their negotiation of the diverse landscape that this field presents.